Clinical relevance and antimicrobial susceptibility profile of the unknown human pathogen Corynebacterium aurimucosum. Issue 3 (18th March 2021) - Lefèvre, Charles R.; Pelletier, Romain; Le Monnier, Alban; Corvec, Stéphane; Bille, Emmanuelle; Potron, Anaïs; Fihman, Vincent; Farfour, Eric; Amara, Marlène; Degand, Nicolas; Barraud, Olivier; Cattoir, Vincent; et al.
Abstract : Introduction. Even though Corynebacterium aurimucosum has been described in 2002, this species has long been underestimated due to the unreliability of conventional identification methods and only a few cases of infections have been reported. Hypothesis/Gap Statement. Little is known about clinical significance and antimicrobial susceptibility profile of this uncommon species. Aim. To evaluate the clinical relevance of C. aurimucosum and its antimicrobial susceptibility profile. Methodology. All C. aurimucosum isolates, collected from 2010 to 2019 in 10 French university hospitals, were retrospectively included. Demographic, clinical and microbiological data were collected for all cases. Antimicrobial susceptibility testing was performed according to the 2019 EUCAST guidelines. Results. Fifty-seven clinical isolates of C. aurimucosum were collected in 57 patients (median age, 65.8 years; male/female sex ratio, 1.1), mostly from urine (28 %), blood culture (28 %) and bone/synovial fluid (19 %) samples. Of them, 14 cases of infection were confirmed, mainly bone and joint infections (50 %) followed by urinary tract infections (UTIs) (21 %), bacteremia (14 %), skin and soft-tissue infections (14 %). C. aurimucosum was recovered in pure culture in 36 % of cases (UTIs and bacteremia) while mixed cultures were observed for other infections. By testing 52 clinical isolates in vitro, this species appeared to be fully susceptible to linezolid and vancomycin while most isolates (>80 %) were susceptible to amoxicillin (MIC90, 2 µg ml −1 ), gentamicin, tetracycline and rifampicin. Both cefotaxime and ciprofloxacin seemed to have a limited activity (ca. 50 % of susceptible strains). The MIC distribution for ciprofloxacin showed a bimodal profile with a population of highly-resistant strains with MICs >2 µg ml −1 . Most isolates (>90 %) were categorized as resistant to penicillin G and clindamycin. Conclusion. C. aurimucosum should be considered as an actual opportunistic pathogen, and treatment with amoxicillin, vancomycin or linezolid should be preferred.